2019
DOI: 10.1080/02770903.2019.1663428
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of autoinjector with accessorized prefilled syringe for benralizumab pharmacokinetic exposure: AMES trial results

Abstract: Objective: We compared the pharmacokinetic exposure following a single subcutaneous dose of benralizumab 30 mg using either autoinjectors (AI) or accessorized prefilled syringes (APFS). APFS and AI functionality and reliability for at-home benralizumab delivery have been demonstrated in the GREGALE and GRECO studies, respectively. Methods: In the open-label AMES study (NCT02968914), 180 healthy adult men and women were randomized to one of two device (AI or APFS) and three injection site (upper arm, abdomen, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
2
10
0
2
Order By: Relevance
“…The mean 1-point improvement in ACQ-6 score during this 28-week study is within the range of improvements observed over 1 year in the SIROCCO and CALIMA studies and over 20 weeks in GREGALE, and indicates clinically important improvement 6,9,14. Furthermore, a nearly complete depletion of blood eosinophils after benralizumab 30-mg injection was observed in GRECO, similar to results in the GREGALE trial and in AMES, a pharmacokinetic study of single-dose benralizumab administration in a clinical setting 6,8,9,14,15. Pharmacokinetics of benralizumab administered via AI were stable during treatment, similar to that observed with APFS in the GREGALE study 14.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The mean 1-point improvement in ACQ-6 score during this 28-week study is within the range of improvements observed over 1 year in the SIROCCO and CALIMA studies and over 20 weeks in GREGALE, and indicates clinically important improvement 6,9,14. Furthermore, a nearly complete depletion of blood eosinophils after benralizumab 30-mg injection was observed in GRECO, similar to results in the GREGALE trial and in AMES, a pharmacokinetic study of single-dose benralizumab administration in a clinical setting 6,8,9,14,15. Pharmacokinetics of benralizumab administered via AI were stable during treatment, similar to that observed with APFS in the GREGALE study 14.…”
Section: Discussionsupporting
confidence: 79%
“…The incidence of AEs related to injection site in GRECO (6.6% of patients) was numerically greater than that observed in the 12-week BISE and 28-week ZONDA studies (up to 3% of patients), 28-week GREGALE study (4% of patients), and 1-year SIROCCO and CALIMA studies (both 2%) 8,14,17. In AMES, incidence of injection-site reactions was even smaller (1% for AI, none reported for APFS) 15…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Such a condition can be translated to asthmatic patients before the next dose administration of a monoclonal antibody. Accordingly with pharmacokinetic studies in healthy subjects (Martin et al, 2019;Shabbir et al, 2019) that received approved doses of monoclonal antibodies (European Medicines Agency, 2015US Food andDrug Administration, 2015, 2017), while the maximum plasma concentrations of benralizumab and mepolizumab were '3 and '12 μg/ml −1 , respectively, the trough concentrations were '1 and '5 μg/ml −1 , respectively. Indeed, our results indicate that at these concentrations both the agents are effective in submaximally inhibiting the airway hyperresponsiveness to histamine in isolated airways.…”
Section: Discussionmentioning
confidence: 99%
“…Such a condition can be translated to asthmatic patients before the next dose administration of a mAb. Accordingly with pharmacokinetic (PK) studies in healthy subjects (Martin et al, 2019;Shabbir et al, 2019) that received approved doses of mAbs (European Medicines Agency, 2015; European Medicines Agency, 2018; US Food and Drug Administration, 2015; US Food and Drug Administration, 2017), while the maximum plasma concentrations of benralizumab and mepolizumab were [? ]3 μg/ml and [?…”
Section: Discussionmentioning
confidence: 99%